Pengaruh E-Book Interaktif terhadap Pemahaman Konsep Siswa pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Minnatul Maula; Budi Febriyanto; Yuyu Yuliati; Rabeka Putri Aini (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The lack of use of varied and innovative teaching materials, especially in IPAS learning, has an impact on students' lack of understanding of concepts. One of the teaching materials that teachers can use in the learning process is an interactive e-book. The purpose of this study was to determine the acquisition of students' concept understanding before and after using interactive e-books in IPAS learning about Changing Energy Forms. The research method used is quantitative, with a pre-experimental design research design. Subjects used by 20 fourth grade students. Data collection techniques using tests, interviews, and questionnaires. The pre-test score obtained an average result of 45.2 while the post-test score obtained an average result of 75.85. Based on the results of research data analysis using the help of SPSS version 27, it can be concluded that the paired sample t-test sig value (2-tailed) of 0.001 <0.05 means Ho is rejected and Ha is accepted. The results showed that there were differences in the acquisition of students' concept understanding before and after using interactive e-books which increased by 30.65 after the use of interactive e-books in learning IPAS Class IV at SDN Babakan Jawa III Majalengka.